Anti-Neoliberal Struggles in the 21st Century: Gramsci Revised - Rebeca Jasso-Aguilar (Partecipazione e Conflitto, 2014)
The dominance of neoliberalism in the past three decades suggests the capacity of capitalism to adapt and restructure itself in periods of crisis and to curb progressive movements that threaten its hegemony. Yet social movements that challenge neoliberalism continue to emerge, sending hopeful signs of its potential demise by ushering in progressive governments that often appear to fall short of expectations. Building off the growing body of research that utilizes Gramscian theory to categorize neoliberalism as a passive revolution, I examine the concept of anti-passive revolution with empirical data to propose a theory of resistance against neoliberalism. The empirical data comes from two movements against neoliberalism: the coalition that challenged the privatization of water in Cochabamba, Bolivia in 2000; and, the movement that challenged the results of the Mexican presidential election in 2006. By examining the trajectories of these movements over a timespan of several years, I identify the empirical conditions for a theory of anti-passive revolution, and the potential for such processes to challenge the hegemony of the passive revolution represented by neoliberalism